Prevalence of Menstrual Migraine among university students and its impact on quality of life: a cross-sectional study - Wong, Jing Ni (2024)
Background: Menstrual migraines, associated with hormonal fluctuations during the menstrual cycle, are a common but underrecognized condition. They can significantly impair daily functioning and quality of life, yet research into their prevalence and impact among university students remains limited, particularly in Malaysia. This study aims to address this gap by exploring the prevalence of menstrual migraines in this population and their effects on physical and mental health, highlighting the importance of tailored interventions to improve well-being.